2017
DOI: 10.1002/jcp.25935
|View full text |Cite
|
Sign up to set email alerts
|

End stage renal disease‐induced hypercalcemia may promote aortic valve calcification via Annexin VI enrichment of valve interstitial cell derived‐matrix vesicles

Abstract: Patients with end‐stage renal disease (ESRD) have elevated circulating calcium (Ca) and phosphate (Pi), and exhibit accelerated progression of calcific aortic valve disease (CAVD). We hypothesized that matrix vesicles (MVs) initiate the calcification process in CAVD. Ca induced rat valve interstitial cells (VICs) calcification at 4.5 mM (16.4‐fold; p < 0.05) whereas Pi treatment alone had no effect. Ca (2.7 mM) and Pi (2.5 mM) synergistically induced calcium deposition (10.8‐fold; p < 0.001) in VICs. Ca treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 41 publications
5
69
0
1
Order By: Relevance
“…In valve interstitial cells, elevated extracellular calcium and phosphate induce release of EVs enriched with Annexin VI [21*]. Similar to its function in vascular SMCs, Annexin VI mediates calcium binding in EVs, promoting mineral formation.…”
Section: Extracellular Vesicles As Mediators Of Cell-matrix Interactionsmentioning
confidence: 99%
“…In valve interstitial cells, elevated extracellular calcium and phosphate induce release of EVs enriched with Annexin VI [21*]. Similar to its function in vascular SMCs, Annexin VI mediates calcium binding in EVs, promoting mineral formation.…”
Section: Extracellular Vesicles As Mediators Of Cell-matrix Interactionsmentioning
confidence: 99%
“…Гиперкальциемия тесно связана с развитием и усугублением течения таких заболеваний, как ате-росклероз, микроангиопатии различного генеза, играет ключевую роль в патогенезе кальциноза аор-тального клапана [6].…”
Section: To Help the Practitionerunclassified
“…Their function continues to be remain controversial since their discovery in 1967 in growth plate cartilage, with some authors attributing these as specimen‐preparation artifacts . Nevertheless, many in vitro and in vivo studies have shown the first mineral crystals in diverse mineralized tissues such as bone, dentin, cartilage, and mineralized vasculature are associated with these structures in the extracellular matrix (ECM) …”
Section: The Phospho1 Mineralization Mechanism: Matrix Vesicle–mediatmentioning
confidence: 99%
“…(56) Nevertheless, many in vitro and in vivo studies have shown the first mineral crystals in diverse mineralized tissues such as bone, dentin, cartilage, and mineralized vasculature are associated with these structures in the extracellular matrix (ECM). (55,(57)(58)(59)(60)(61)(62)(63) The structure and function of MVs in skeletal and vascular mineralization has recently been reviewed by several authors. (53,(64)(65)(66)(67) The biogenesis of these vesicles may occur through multiple proposed mechanisms; however, the most prevalent theories include polarized budding from the parental cell membrane, or from microvilli on the cell surface, as demonstrated in hypertrophic chondrocytes and SaOS-2 osteoblast-like cells.…”
Section: The Phospho1 Mineralization Mechanism: Matrix Vesicle-mediatmentioning
confidence: 99%